Study of Soil Contamination by Toxocara Spp. Eggs in Fasa, South of Iran from April to December 2018 - fatemeh rastgoo; zahra rostaee; fatemeh mosleh; Arash Hasannezhad; Hooshmand Ghorbaani Barnaaji; ahmad abolghazi (Fasa University of Medical Sciences, 2019)
Background & Objective: Toxocariasis is a parasitic disease caused by dog ​​ascaris and cat ascaris. Raising pets, especially dogs or cats, has been part of modern life and this raising is the cause of soil contamination by Toxocara spp. eggs. Contacted with contaminated soil is considered the main reservoir of transmission of Toxocara infection to humans. This survey was carried out to clarify the current status of soil contamination by Toxocara spp. eggs.  Materials & Methods: Soil contamination by Toxocara spp. eggs was surveyed in Fasa from April to December 2018. In this study, 56 soil samples were collected from 10 public parks in Fasa. The soil samples were provided by the flotation method and examined by a microscope. Results: The results of this study showed that six (60%) of 10 parks were contaminated by Toxocara eggs. Out of 56 samples collected, 54 Toxocara spp eggs were found. Conclusion: High prevalence of Toxocara spp. eggs in soil samples of this study can be associated with the rising population of stray dogs or cats and pets in public parks, the carriers of adult worms and the active source of soil contamination.